POTRAIT OF REPRODUCTIVE MANAGEMENT IMPLEMENTATION ON BUFFALO BREEDING IN BOMBANA DISTRICT - Nafiu, La Ode; Saili, Takdir (Proceeding Buffalo International Conference, 2013)
Buffalo production is one of the alternative livestock production in attempt to reach meat self-sufficiency program in 2014. Production system of buffalo in Bombana district was still under traditional management in which buffalo are kept in free range system. This study aimed to describe the reproductive management of buffalo breeding in Bombana District. The survey was conducted on the mainland and islands of Bombana district, involved 80 farmers that consisted of 60 farmers in the mainland and 20 farmers in the islands. Some parameters reflected the reproductive management aspects were observed. The results showed that: (1) there was only 50% of farmers who arranged the first mating of their buffalo cows, (2) 66% buffalo cows were first mated at the age of 2-3 years, 22.50% mated over 3 years, and only 11.25% mated under the age of 2 years, (3) 61.25% buffalo cows calving for the first time at the age of 3-4 years and 38.75% over 4 years, (4) 45% had calving interval <1.5 years, 27.50% ranging from 1.5 - 2.0 years and 27.50% was > 2 years, (5) 100% buffalo were natural mating, and (6) 31.25% of farmers did not know the signs of estrus in buffalo.Â  In conclusion, implementation of reproductive management of buffalo breeding in Bombana was still low. Application of reproductive management by farmers in the mainland areas was better than the islands.